CORRELATION BETWEEN NEURON-SPECIFIC ENOLASE (NSE) SERUM LEVEL AND TRAUMATIC BRAIN INJURY SEVERITY - Pitra, Dian Ayu Hamama; Syafrita, Yuliarni; Susanti, Rika; Rita, Rauza Sukma (Nusantara Hasana Journal, 2025)
Traumatic brain injuries (TBIs) are a health and socio-economic problem worldwide, both in low- and high-income countries, that affects all age groups. Computed Tomography (CT) is a diagnostic modality that can be used to assess brain damage. However, there are some limitations in the use of CT in TBIs. Therefore, biomarkers are expected to be a solution to identify brain injuries. Neuron-Specific Enolase (NSE) is a more practical and cheaper alternative. It does not require patient mobilization, especially for patients with severe TBIs, to accompany clinical examinations and CT. Methods: A cross-sectional design was used to determine the correlation between Neuron Specific Enolase (NSE) serum levels and the severity of TBIs at RSUP Dr. M. Djamil, Padang. Results: The study found that most patients were 23 men (76.7%), consisting of adults (40.0%). The majority of patients had mild traumatic brain injury (GCS 13-15) in 18 people (60.0%). The cut-off point for serum NSE was 6.6 ng/ml using the ROC curve. There was a negative correlation between serum NSE levels and the severity of TBI (r=-0.211). Conclusion: The correlation of serum NSE levels with the severity of TBI was very weak.